EFEKTIVITAS MODEL COOPERATIVE LEARNING TIPE JIGSAW DALAM MENINGKATKAN HASIL PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM PADA PESERTA DIDIK KELAS VIII MTS ARIFAH KABUPATEN GOWAO - Ismunandar; Bunyamin, Andi; Mustamim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine how the implementation of the Jigsaw-type Cooperative Learning model can improve learning outcomes in Islamic Cultural History (SKI) among eighth-grade students of MTs Arifah Gowa, Pallangga District, Pangkabinanga Subdistrict. The type of research used in this undergraduate thesis is descriptive quantitative research. The quantitative method is referred to as a traditional method because it has long been widely used and has become a conventional approach in research. It is called quantitative because the research data are presented in numerical form and analyzed using statistical techniques. As implied by its name, descriptive research aims to describe, explain, and validate the phenomena under investigation. The implementation of the Jigsaw-type Cooperative Learning model in teaching Islamic Cultural History (SKI) to eighth-grade students at MTs Arifah Gowa, Pallangga District, Pangkabinanga Subdistrict, was carried out through systematic learning stages, including the formation of heterogeneous home groups, distribution of learning materials to each group member, formation of expert groups, discussion of materials within expert groups, and the re-presentation of the material to the home groups. During the implementation process, students were actively involved in discussions, presentations, and cooperative group activities. Each student was responsible for understanding and conveying the portion of the material assigned to them, thereby fostering positive interactions among students. The teacher acted as a facilitator by guiding the learning process and providing reinforcement of the material.The effectiveness of the Jigsaw-type Cooperative Learning model in improving SKI learning outcomes can be observed through a comparison of students’ learning results before and after the implementation of the learning model. The results of the study indicate an improvement in students’ learning outcomes following the application of the Jigsaw model